RUBBER TAPPER TERRITORY: EXPERIENCES AND CHALLENGES IN THE JACI-PARANÁ EXTRACTIVE RESERVE, RONDÔNIA - da Silva Santana, Ravele; Guimarães, Siane Cristhina Pedroso (Seven Editora, 2025)
This article analyzes the experiences and challenges faced by rubber tappers in the Jaci-Paraná Extractive Reserve (Resex), in Rondônia, considering the conflicting territorial dynamics between environmental conservation and the expansion of the agricultural frontier in this area. The research, based on a qualitative approach and dialectical analysis, uses primary and secondary data to discuss the resistance of traditional communities in the face of pressure from economic agents and the omission of the State. The results highlight the weakening of the extractivist way of life due to deforestation, land grabbing, and the lack of effective public policies. It is concluded that guaranteeing the territorial rights of rubber tappers requires integrated actions in environmental management, land regularization, and the strengthening of community organization.DOI: https://doi.org/10.56238/sevened2025.029-062